XÁC ĐỊNH CÁC ĐỨT GÃY HOẠT ĐỘNG ĐỆ TỨ - HIỆN ĐẠI Ở TÂY BẮC VIỆT NAM THEO DỊCH CHUYỂN ĐỊA HÌNH VÀ ĐỊA MẠO CẤU TRÚC - Thôn, Nguyễn Thế; Thắng, Trần Văn (Vietnam Journal of Earth Sciences, 2005)
The North-West region of Vietnam, a complicated geological region currently is under compressive conditions and has many quaternary - recently active faults. The paper introduces quaternary - recently active faults based on the study of the relief vertical and horizontal movement and the geomorphologic structure. The paper also presents the relationship between the faults’ activity and their seismic potential. Besides the paper also introduces the mechanism of the active faults’ formation in the North-West region of Vietnam.